Cytotoxicity of V30M and L55P Transthyretin Variants on Human Cells - Annanon , Siripa; Prapunpoj, Porntip (Burapha Science Journal, 2026)
Transthyretin (TTR) is one of the thyroxine transport protein in the plasma and cerebrospinal fluid. It is a 55-kDa homotetrameric protein. The mutation of TTR gene that leads to a single amino acid change of TTR protein will result in the TTR variant, which is the major cause of TTR amyloidosis. TTR mis-folding into toxic amyloid fibril found deposited and resulting in dysfunction of the nervous system. Among the identified TTR variants, V30M (methionine for valine substitution at position 30) is the most common type; whereas, L55P (proline for leucine substitution at position 55) is the most aggressive type. To evaluate amyloidogenicity of TTR variants, cytotoxicity assay is a primary assessment; however, the sensitivity and specificity of cell to TTR amyloid are the effectiveness factors of the assay. The objective of this research is to comparatively study on the responsiveness of human cell types to the toxicity of TTR amyloid in order to identify more cell that is sensitive and appropriate for using as a tool in the study of TTR amyloidosis. By using recombinant V30M and L55P as tools, it revealed that L55P was induced by acidic condition to form a soluble aggregate faster than V30M, and it was more toxic to the studied cells including fibroblasts (F‑N and F-DS), neuroblast (LAN-5) and lymphoblast than V30M. In addition, the comparatively results showed that F-DS cells were the most sensitive to the toxicity of soluble aggregated TTRs.